Advanced radiation protection dosimetry - Dewji, Shaheen A.; Hertel, Nolan E., 1950- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"Although many radiation protection scientists and engineers use dose coefficients, few know the origin of those dose coefficients. This is the first book in over 40 years to address the topic of radiation protection dosimetry in intimate detail. It covers all methods used in radiation protection dosimetry, including advanced external and internal radiation dosimetry concepts and regulatory applications. It is an ideal reference for both scientists and practitioners in radiation protection and students in graduate health physics and medical physics courses"--
Fundamental concepts and quantities -- Evolution of radiation protection guidance in the United States -- Radiation detection and measurement -- Reference individuals defined for external and internal radiation dosimetry -- Biokinetic models -- Dosimetric models -- Dose coefficients -- Cancer risk coefficients -- Interpretation of bioassay results to assess the intake of radionuclides.
OCLC-licensed vendor bibliographic record.
Keywords: Radiation dosimetry; Radiation -- Safety measures; MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; SCIENCE / Physics; MEDICAL / Radiology & Nuclear Medicine; MEDICAL / Biotechnology